2011
DOI: 10.1118/1.3656077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a human‐tissue‐like phantom for 3.0‐T MRI

Abstract: Adjustment of GdCl(3) and agarose concentrations allows arbitrary setting of relaxation times, and the creation of a phantom that can mimic relaxation times of human-tissue. Carrageenan is considered the most suitable as a gelling agent for an MRI phantom, as it permits the relatively easy and inexpensive production of a large phantom such as for the human torso, and which can be easily shaped with a knife.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…Although the goal of this study was to develop phantoms with specific dielectric properties, a phantom that additionally replicates in vivo relaxation properties may be valuable for comprehensive MRI protocol development. Ingredients such as agarose can be used to control T 2 , while gadolinium , nickel or copper , or manganese chloride have been utilized to modify T 1 . However, these ingredients additionally influence conductivity, which necessitates a more complex recipe than that proposed here to simultaneously achieve the desired conductivity, permittivity, and T 1 and T 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the goal of this study was to develop phantoms with specific dielectric properties, a phantom that additionally replicates in vivo relaxation properties may be valuable for comprehensive MRI protocol development. Ingredients such as agarose can be used to control T 2 , while gadolinium , nickel or copper , or manganese chloride have been utilized to modify T 1 . However, these ingredients additionally influence conductivity, which necessitates a more complex recipe than that proposed here to simultaneously achieve the desired conductivity, permittivity, and T 1 and T 2 .…”
Section: Discussionmentioning
confidence: 99%
“…These interactions cause constructive and destructive interference patterns that depend on the shape and dielectric properties of the object. Traditional MRI phantoms that replicate tissue relaxation properties (T 1 and T 2 ) may not be appropriate for certain image protocol development at high field strengths if they yield an electromagnetic field distribution that is not representative of in vivo situations. The purpose of this work is to prepare and characterize phantoms with tissue‐equivalent dielectric properties that are suitable for MRI or wireless applications.…”
Section: Introductionmentioning
confidence: 99%
“…Various MRI and MRS phantoms have been developed for metabolite quantification (Rice et al, 1998;Simmons et al, 1998), relaxation times of human brain tissue (Rice et al, 1998), angiography (Krämer et al, 2004), MRI human tissue equivalent (Hattori et al, 2013;Kato et al, 2005;Ikemoto et al, 2011), reproducibility of geometric distortion in MRI (Mizowaki et al, 2000), high-resolution phantom for MRI (Fellner et al, 2001), and MRS QA phantom (Woo et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Ohno et al [21] showed that when agarose gel concentration was reduced to enable longer T2 relaxation times, the gel matrix lost structural integrity and became unstable. Ikemoto et al [13] and Yoshimura et al [22] combined carrageenan and agarose to achieve longer T2 times and maintain strength and stability of phantoms. Ikemoto et al [13] and Yoshimura et al [22] combined carrageenan and agarose to achieve longer T2 times and maintain strength and stability of phantoms.…”
Section: Customizing Density and T2 Relaxation Timesmentioning
confidence: 99%
“…Previous investigators used agarose-or carrageenanbased products for constructing stable solid-phase homogeneous matrices [11,13]. For MRI, combinations of paramagnetic ions and chelators yield the desired T2 relaxation time by spoiling phase coherence of proton magnetization through spin-spin interactions.…”
Section: Introductionmentioning
confidence: 99%